2019
DOI: 10.1111/ijcs.12511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of food labelling usefulness for consumers

Abstract: Food labelling is a means of communication between food business operators and consumers, representing an important factor in consumer purchasing decisions. The enforcement of the new food labelling policy is aimed to improve food safety and public health through the mandatory indication of information and nutritional values. To understand the usefulness of the information provided for consumers, a survey was carried out to assess the efficacy of the information presented in food labelling. Principal component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 15 publications
1
39
1
1
Order By: Relevance
“…A sample of non-institutionalized, English-speaking adults aged 55 years and older, who reside in the United States (US), participated in the study. This segment was selected because older adults are affected by cancer and other chronic diseases outlined in QHCs [16,24,25]. They also represent a large portion of the population with robust purchasing power [26,27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of non-institutionalized, English-speaking adults aged 55 years and older, who reside in the United States (US), participated in the study. This segment was selected because older adults are affected by cancer and other chronic diseases outlined in QHCs [16,24,25]. They also represent a large portion of the population with robust purchasing power [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…One study found that more detailed messages had stronger impacts on consumers when the nutrient or diet–disease link was less familiar [14]. Research also indicates that US consumers have a limited ability to act on scientific information [15] and rarely read labels because of excessive information and a lack of time [16], and these reasons may be why QHCs are infrequently found on labels [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…(2018) showed that young people who valued food production practices such as organic, not processed, locally grown and not genetically modified were far more likely to value GF food. For specific consumer groups, such as athletes, those with health conditions (such as food allergies), or those seeking a healthy lifestyle, food labelling was observed to be more useful (Moreira, Garcia‐Díez, de Almeida, & Saraiva, 2019). In the case of patients of CD or other gluten‐related diseases, GF labelling is one of the most important determinants of food product choices (Zysk et al., 2019).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In previous research, food label use was associated with consumer characteristics, product type, and purchasing context. The following variables were found to affect reading labels: gender [ 1 , 2 , 3 , 4 , 5 ], age [ 4 , 6 ], marital status [ 7 ], ethnicity [ 2 ], socioeconomic status [ 2 , 7 ], including education level [ 4 , 5 , 7 , 8 , 9 ], professional activity [ 9 ], income [ 5 ], place of living—rural or urban areas [ 2 , 5 ], Body Mass Index [ 2 , 4 ], being an athlete [ 10 ], food-related motivation [ 11 ], nutrition knowledge [ 4 , 12 , 13 ], self-reported health [ 4 , 10 ], having a special diet [ 4 , 9 ], being concerned with a healthy lifestyle [ 10 ], attitude towards the health value of the products [ 13 ], health orientation [ 14 ], taste [ 9 , 13 ], price [ 9 ], product specificity [ 12 ], buying the product for the first time [ 12 ], the amount of time spent shopping [ 9 ], and buying organic food [ 15 ]. There are various connections between these predictors, e.g., the gender effect is mainly due to differences in nutrition knowledge levels [ 12 ].…”
Section: Introductionmentioning
confidence: 99%